Ecological assessment of an intermitent Mediterranean river using community structure and function: evaluating the role of different organism groups - Hughes, Samantha Jane (2009)
1. Reliable lotic ecological monitoring requires knowledge of river typology, environmental factors, the effect of stressors known here as ‘pressures’ and appropriate indicators of anthropogenically induced change. We sampled benthic macroinvertebrate, fish, bird and macrophyte communities along an intermittent Mediterranean river and analysed community structure (relative abundance) and function (metrics) relative to environmental and pressure gradients in order to identify suitable indicator group(s) for future monitoring and mitigation programmes. 2. Principal components analysis revealed that scale-dependent longitudinal differences in valley form separated narrower higher lying sites and tributaries with good quality habitats from more open degraded sites lower down the river continuum on a small floodplain and large scale pressures describing changes in land use related to agriculture with associated physical bankside and channel impacts. 3. Forward selection of variables in redundancy analysis (RDA) showed that reach scale environmental variables were selected more frequently than pressure variables for each organism group. Altitude and pH were highly redundant within and between groups, indicating essentially longitudinal structural and functional distribution patterns. Redundancy was far lower between selected pressure variables, but single or no pressure variables were retained for some organism groups indicating poor association of functional data, in particular, with the identified pressures. All RDA results indicated a longitudinal pH gradient, highlighting the combined effect of multiple environmental and pressure based mechanisms on organism groups. 4. Large, mobile organisms such as fish and birds provided a reliable link between organism structure and function, environmental factors and physical disturbance of the channel, bankside and wider river corridor. Benthic macroinvertebrate and macrophyte structural data revealed distribution patterns in relation to water velocity, a key parameter for developing appropriate compensation measures. 5. Results clearly show the importance of assessing patterns of both functional and structural change across multiple organism groups in order to identify typologically appropriate links with complex environmental and pressure gradients and develop and implement appropriate monitoring systems